Placental lesions associated with abortion and stillbirth in goats naturally infected by Neospora caninum - Mesquita,Leonardo P. (2018)
ABSTRACT: Neospora caninum has been described as a parasite that sporadically causes reproductive problems in goats. Several aspects of the pathogenesis of neosporosis in naturally infected goats remain to be established. The aims of the present study were to characterize the placental lesions in goats naturally infected by N. caninum and to evaluate several diagnostic techniques for effective detection of this protozoan in the goat placenta. Some placentas in this study originated from abortion and stillbirth in which there were severe lesions. The lesions were characterized mainly by necrosis involving the mesenchyme of the chorionic villi and trophoblast cells often alongside mononuclear inflammation and in some cases with neutrophilic infiltration. N. caninum DNA was detected in these placentas, but parasite structures were not visualized through immunohistochemistry (IHC). However, five of 11 placentas from N. caninum-infected goats that gave birth to healthy kids had histological lesions characterized by mononuclear inflammation. Of these 11 placentas, N. caninum DNA was detected in seven, and N. caninum tachyzoites were detected in only one of these seven placentas using IHC. The present study demonstrates that severe lesions in the placenta are associated with abortion and stillbirth in caprine neosporosis and the placental alterations are likely involved in abortion pathogenesis. Moreover, the results highlight the importance of using more than one diagnostic technique for the detection of the protozoan in placentas because N. caninum cannot be reliably detected by histological and immunohistochemical tests.